(untitled) (Educational Perspectives Magazine (REPED), 2022)
This presentation develops some reflections on the teacher education of elementary school teachers during the last 20 years in Chile. The type of relationships established between formation institutions and educational poücies is emphasized. Particularly, teachers are viewed as main participants in a social device through which the society tries to prepare new generations for the adult life. The type of formation required for our elementary teachers within a contemporary social context and the disciplines’ demands raised from the national curriculum are exhibit.